Steganacarus (Tropacarus) carinatus subsp. carinatus carinatus (C. L. Koch 1841 - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 258, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444

Steganacarus (Tropacarus) carinatus carinatus (C.L. Koch, 1841) * Material – New record for Turkey. Two specimens in Aluçdağı National Park, N 40° 49′ 75.37′′, E 32° 58′ 26.46′′, alt. = 1402 m, 17 July 2018, soil. Global distribution – Palaearctic. Ecology – All types of habitats.
Keywords: Arthropoda; Phthiracaridae; Steganacarus carinatus; Arachnida; Animalia; Biodiversity; Sarcoptiformes; Steganacarus (tropacarus) carinatus carinatus (c.l. koch, 1841); Steganacarus; Taxonomy; 15. Life on land